Analisis Pendapatan Pengemudi Ojek Online Pada Masa Pandemi Covid-19 di Kota Salatiga - Mallo, Heber Andrew Riyan; Nugroho, Paskah Ika (Universitas Pendidikan Ganesha, 2021)
Go-Jek is an online-based transportation service provider that uses an accounting information system. Physical distancing is applied to reduce the spread of the coronavirus by the government which has an impact on the transportation sector. The purpose of this study was to analyze the income of Go-Jek company online drivers in the city of Salatiga during the COVID-19 pandemic with two main services during the pandemic, GoRide and GoFood. This study involved 20 Go-Jek drivers who were interviewed, 10 drivers for GoRide services and 10 drivers for GoFood services. The results showed that even though the COVID-19 pandemic caused a decrease in income for drivers, GoRide service drivers did not experience a significant decrease compared to GoFood service drivers.